Air flow exchange velocity of urban canyon cavities due to thermal spatial differences - Panão, Marta Oliveira (2010)
In this paper, the air exchange velocity between the urban canyon cavity and the air layer above roof level is quantified, using a two-dimensional k-ε model, and correlated with the air cavity mean temperature, for two cases: leeward and downward wall heating. The spatial thermal differences are evaluated by assuming a wall temperature higher than the air temperature, with this difference ranging between 0 and 16 K. The undisturbed wind velocity above the roof level is varied from 1 to 6 ms-1 and the canyon aspect ratio is 1.5, which corresponds to a skimming flow regime. The model predicts two situations, which correspond to air flow regimes where one or two eddies are formed, respectively: (a) for high wind speed, the air inside the cavity is negligible affect by the buoyancy effect and the air exchange velocity linearly increases with the increase of wind velocity; (b) for low wind speed, when the buoyancy forces are stronger than the wind induced forces, the air exchange velocity is not a linear function with the wind velocity. The transition wind velocity between (a) and (b) is a function of the wall-air temperature difference. The situation of windward heated wall and two eddies air flow regime is the most favorable to extract heat from the cavity. On the contrary, the heated air is hardly extracted from the cavity when only the wind induced eddy is predicted and windward wall is heated. In this situation an increase of 10 K on the wall temperature increases by 1 K the in-cavity air temperature.